2015
DOI: 10.17795/jjnpp-23770
|View full text |Cite
|
Sign up to set email alerts
|

Punica granatum Peel Extract Toxicity in Mice

Abstract: Background: Pomegranate (Punica granatum) is a significant source of bioactive compounds. However, its toxicity is not intensively studied. Objectives: The current study investigated the safety and tolerability of pomegranate peel extract (PPE) in BALB/c mice. Materials and Methods: A total of 25 female BALB/c mice were randomly grouped. Each experimental group consisted of five animals. Repeated doses including 0.5, 1.9 and 7.5 mg/kg body weight of PPE were gavaged to BALB/c mice, for 22 days and the single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Bassiri Jahromi et al [18] found that administration of PEE (repeated doses of 0.5, 1.9, and 7.5 mg/kg body weight) to mice did not produce any irritation to oral mucosa or respiratory passage. Further, single intradermal injection (224 mg//kg) of the extract was found to be safe without any manifestation of skin allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Bassiri Jahromi et al [18] found that administration of PEE (repeated doses of 0.5, 1.9, and 7.5 mg/kg body weight) to mice did not produce any irritation to oral mucosa or respiratory passage. Further, single intradermal injection (224 mg//kg) of the extract was found to be safe without any manifestation of skin allergy.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of extracts from P. granatum on S. papillosus larvae is currently unstudied. Jahromi et al (2015) studied the safety of the extract of pomegranade peel for mice. Doses of 0.5, 1.9 and 7.5 mg/kg of body weight introduced over 22 days displayed no toxic effect according to clinical signs and histopreparations.…”
Section: Introductionmentioning
confidence: 99%
“…None of the animals developed any hematological or biochemical abnormalities, and all mice survived until the end of the study. Additionally, no allergic reaction was shown after 24, 48, and 72 h. 122 The study found that pomegranate peel, a natural extract with excellent anti-inflammatory and antioxidant activities, was potent against autoimmune hepatitis (AIH) in a ConAinduced AIH mouse model. The results showed that PPE had substantial anti-inflammatory and protective effects on the occurrence and development of AIH.…”
Section: Acsmentioning
confidence: 95%